H.C. Zentgraaff contra het echtpaar Székely-Lulofs: Wie was die man? - Termorshuizen, Gerard (Acta Neerlandica, 2016)
In 1931 and 1932, Madelon Lulofs published her novels Rubber and Koelie; in 1935 Van oerwoud tot plantage appeared, a translation of the novel Őserdőktől az ültetvényekig by her spouse, László Székely, that came out in the same year. The novels give a realistic and revealing look into the harsh life on the plantations of Deli at the East Coast of Sumatra. Although the books were generally well received in the Netherlands and were considered by progressive critics to be accusations against the colonial administration, the Dutch East Indian press responded with indignation: the colony, as they concluded, was put in a bad light, which created a wrong impression amongst the general public abroad. Besides, equally importantly, these novels served as an evidence of colonial oppression for Indian nationalists, they argued. The Székely-Lulofs couple was heavily rebuked for it. The hate campaign against them was led by journalist H.C. Zentgraaff.